Disaster Nursing: Trends in the Professional Literature. Issue Volume 34:Issue s1(2019) (May 2019) - Cohen, Odeya; Stewart, David; Kanbara, Sakiko; Catton, Howard; Shamian, Judith
Abstract : Introduction: Nurses' broad knowledge and treatment skills are instrumental to disaster management. Roles, responsibilities, and practice take on additional dimensions to their regular roles during these times. Despite this crucial position, the literature indicates a gap between their actual work in emergencies and the investment in training and establishing response plans. Aim: To explore trends in disaster nursing reflected in professional literature, link these trends to current disaster nursing competencies and standards, and reflect based on the literature how nursing can better contribute to disaster management. Methods: A systematic literature review, conducted using six electronic databases, and examination of peer-reviewed English journal articles. Selected publications were examined to explore the domains of disaster nursing: policy, education, practice, research. Additional considerations were the scope of the paper: local, national, regional, or international. The International Nursing Councils' (ICN) Disaster-Nursing competencies are examined in this context. Results: The search yielded 171 articles that met the inclusion criteria. Articles were published between 2001 and 2018, showing an annual increase. Of the articles, 48% (n = 82) were research studies and 12% (n = 20) were defined as dealing with management issues. Classified by domain, 48% (n = 82) dealt with practical implications of disaster nursing and 35% (n = 60) discussed educational issues. Only 11% of the papers reviewed policy matters, and of these, two included research. Classified by scope, about 11% (n =18) had an international perspective. Discussion: Current standards attribute a greater role to disaster-nursing in leadership in disaster preparedness, particularly from a policy perspective. However, this study indicates that only about 11% of publications reviewed policy issues and management matters. A high percentage of educational publications discuss the importance of including disaster nursing issues in the curricula. In order to advance this area, there is a need to conduct dedicated studies.